1998
DOI: 10.1148/radiology.208.1.9646801
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenopathy: differentiation of benign from malignant disease--color Doppler US assessment of intranodal angioarchitecture.

Abstract: Color Doppler US is a reliable and reproducible method for help in the differentiation between reactive and malignant alterations of superficial lymph nodes by using findings of intranodal angioarchitecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
1
12

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 0 publications
7
105
1
12
Order By: Relevance
“…More detailed classification patterns were described by Na et al [10] and Tschammler et al [11]. Tschammler et al added descriptions of features that are typical of reactive nodes: the presence of a longitudinal vessel, peripheral branches originating from the longitudinal vessels, small intranodal color dots representing short vessel segments [11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…More detailed classification patterns were described by Na et al [10] and Tschammler et al [11]. Tschammler et al added descriptions of features that are typical of reactive nodes: the presence of a longitudinal vessel, peripheral branches originating from the longitudinal vessels, small intranodal color dots representing short vessel segments [11].…”
Section: Discussionmentioning
confidence: 99%
“…Na et al added more detailed descriptions: deformed radial and aberrant multifocal patterns [10]. Apart from the presence of subcapsular vessels, Tschammler et al reported the following findings as typical of malignant lymph nodes: displaced (curved) intranodal vessels, focal absence of perfusion, and aberrant vessels (one or more central vessels, excluding longitudinal vessel branches, forming an angle of 30 with the skin surface or with the longitudinal axis of the lymph node) [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations